2018
DOI: 10.1093/cercor/bhy175
|View full text |Cite
|
Sign up to set email alerts
|

ACC Sulcal Patterns and Their Modulation on Cognitive Control Efficiency Across Lifespan: A Neuroanatomical Study on Bilinguals and Monolinguals

Abstract: The anterior cingulate cortex (ACC) is a key structure implicated in the regulation of cognitive control (CC). Previous studies suggest that variability in the ACC sulcal pattern-a neurodevelopmental marker unaffected by maturation or plasticity after birth-is associated with intersubject differences in CC performance. Here, we investigated whether bilingual experience modulates the effects of ACC sulcal variability on CC performance across the lifespan. Using structural MRI, we first established the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 83 publications
0
24
2
Order By: Relevance
“…dorsal and parallel to the cingulate sulcus (CS) on the medial surface of the ACC (Ono et al, 1990;Paus et al, 1996;Yücel et al, 2001). Here, following Ono and colleagues' nomenclature (Ono et al, 1990), as in our previous studies (Cachia et al, 2017;Del Maschio et al, 2019), two types of dACC sulcation were identified depending on the PCS occurrence in each hemisphere: a ''single'' type (CS only) and a ''double parallel'' type (CS and additional PCS) ( Fig. 1a, b).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…dorsal and parallel to the cingulate sulcus (CS) on the medial surface of the ACC (Ono et al, 1990;Paus et al, 1996;Yücel et al, 2001). Here, following Ono and colleagues' nomenclature (Ono et al, 1990), as in our previous studies (Cachia et al, 2017;Del Maschio et al, 2019), two types of dACC sulcation were identified depending on the PCS occurrence in each hemisphere: a ''single'' type (CS only) and a ''double parallel'' type (CS and additional PCS) ( Fig. 1a, b).…”
mentioning
confidence: 84%
“…Following Garrison's PCS measurement protocol (Garrison, 2017), first reported in Garrison and colleagues (2015), all T1 images were imported into MANGO (Multiimage Analysis GUI, v 4.0, http://ric.uthscsa.edu/mango/ mango.html, The University of Texas Health Science Center; see also Del Maschio et al, 2019). The CS was identified at 4 mm laterally from the midline (x = 0) on either hemisphere, lying dorsal to the corpus callosum.…”
mentioning
confidence: 99%
“…Late, older adult bilinguals were faster overall and had less skewed RT distributions on incongruent trials on the Flanker task compared to older adult monolinguals (Abutalebi et al, 2015). Age-related performance declines on ANT and Flanker tasks were larger in monolinguals than in bilinguals (Borsa et al, 2018;Del Maschio et al, 2019), indicating that only monolinguals became more susceptible to interference from distractors with age. Across the lifespan, bilinguals produce fewer total errors on the Stroop task (Massa et al, 2020) and have a smaller Stroop effect than monolinguals (Bialystok et al, 2008;Incera and McLennan, 2018), even after accounting for bilinguals' reduced automaticity of word processing (Bialystok et al, 2008).…”
Section: Effects Of Multilingualism On the Cingulo-opercular Network mentioning
confidence: 87%
“…Moreover, aging was associated with decreased gray matter volume of IFG bilaterally in monolinguals, but only in the left-hemisphere for bilinguals (Borsa et al, 2018). These structural changes in older multilingual adults are accompanied by diminished cognitive decline (e.g., less age-related slowing on the Flanker task; Abutalebi et al, 2015;Del Maschio et al, 2019) and altered structure-function relationships between cingulo-opercular regions and cognitive control (Borsa et al, 2018;Del Maschio et al, 2019). For instance, higher ACC volume was associated with smaller conflict effects on the ANT in middle-aged to older bilinguals but not in monolinguals (Borsa et al, 2018), indicating that ACC is related to cognitive control function during healthy aging for bilinguals only.…”
Section: Effects Of Multilingualism On the Cingulo-opercular Network mentioning
confidence: 98%
See 1 more Smart Citation